Local Financial Development and Capital Accumulations: Evidence from Turkey - Eryiğit, Sibel Balı; Eryiğit, Kadir Yasin; Dülgeroğlu, Ercan (Panoeconomicus, 2015)
Despite the unquestionable importance of financial markets in the economy, the factors promoting financial development have just recently begun to be researched intensively. In this context, the aim of the study is to explain the reasons for the financial development gaps among provinces in Turkey on the basis of capital accumulations. According to the results of the spatial panel data model estimates based on indices of 81 provinces in Turkey for the period 2005-2009, it was found that the level of social capital best explained the level of financial development, followed by physical capital and human capital. Additionally, it was found that capital accumulations contributed above average not only to the financial development of that province, but also to that of the surrounding provinces.Key words: Financial development, Physical capital, Human capital, Social capital, Spatial panel data analysis.JEL: C21, C23, C43, G20, O16, R12.